Assessment of the Impact of the Economic Potential of Regions on the Living Standards of the Population - M. Yu. Makhotaeva; M. A. Nikolaev (Финансы: теория и практика, 2025)
The purpose of the paper is to assess the impact of the region’s economic potential on the standard of living and to develop tools to improve the efficiency of using the financial potential of a constituent entity of the Russian Federation. The object of the study is the regions of the Russian Federation, and the subject is their economic potential and standard of living. At the first stage, we considered the impact of the resource potential of the regions of the Central and Northwestern Federal Districts based on the use of correlation and regression analysis. Modeling has shown that for the regions of the Central and Northwestern Federal Districts, the most significant impact on the standard of living is provided by investment and innovation potentials. In addition, for the Central Federal District, production and labor potentials also have a significant impact, and for the Northwestern Federal District, the general economic potential, represented by the GRP indicator, is significant. In the second stage, we used the k-means method to cluster 85 regions based on the size of their resource potential and standard of living. The analysis showed that most regions have a standard of living that corresponds to and even exceeds the existing economic potential. This situation seems quite natural, since the standard of living in a region is determined not only by the potential of the territory, but also by the potential of the state as a whole. The assessment of the financial reserve available to the regions is based on the concept of fiscal space, which allows assessing the possibilities of mobilizing additional own and borrowed financial resources to address priority issues of the socio-economic development of the territory. The proposed typology of regions by standard of living and by the size of the fiscal space can be used as a tool for assessing the potential of the fiscal space of the region to address the current socio-economic problems of the territory.